Novel role for carbohydrate responsive element binding protein in the control of ethanol metabolism and susceptibility to binge drinking. Issue 4 (6th May 2015) - Marmier, Solenne; Dentin, Renaud; Daujat‐Chavanieu, Martine; Guillou, Hervé; Bertrand‐Michel, Justine; Gerbal‐Chaloin, Sabine; Girard, Jean; Lotersztajn, Sophie; Postic, Catherine
<x xml:space="preserve">Abstract</x> Carbohydrate responsive element binding protein (ChREBP) is central for de novo fatty acid synthesis under physiological conditions and in the context of nonalcoholic fatty liver disease. We explored its contribution to alcohol‐induced steatosis in a mouse model of binge drinking as acute ethanol (EtOH) intoxication has become an alarming health problem. Within 6 hours, ChREBP acetylation and its recruitment onto target gene promoters were increased in liver of EtOH‐fed mice. Acetylation of ChREBP was dependent on alcohol metabolism because inhibition of alcohol dehydrogenase (ADH) activity blunted ChREBP EtOH‐induced acetylation in mouse hepatocytes. Transfection of an acetylation‐defective mutant of ChREBP (ChREBPK672A) in HepG2 cells impaired the stimulatory effect of EtOH on ChREBP activity. Importantly, ChREBP silencing in the liver of EtOH‐fed mice prevented alcohol‐induced triglyceride accumulation through an inhibition of the lipogenic pathway but also led, unexpectedly, to hypothermia, increased blood acetaldehyde concentrations, and enhanced lethality. This phenotype was associated with impaired hepatic EtOH metabolism as a consequence of reduced ADH activity. While the expression and activity of the NAD+ dependent deacetylase sirtuin 1, a ChREBP‐negative target, were down‐regulated in the liver of alcohol‐fed mice, they were restored to control levels upon ChREBP silencing. In turn, ADH acetylation was reduced, suggesting that ChREBP regulates EtOH metabolism and ADH activity through its direct control of sirtuin 1 expression. Indeed, when sirtuin 1 activity was rescued by resveratrol pretreatment in EtOH‐treated hepatocytes, a significant decrease in ADH protein content and/or acetylation was observed. Conclusion: our study describes a novel role for ChREBP in EtOH metabolism and unravels its protective effect against severe intoxication in response to binge drinking. (Hepatology 2015;62:1086‐1100)